Prawdziwy turysta u schyłku belle époque. Niezwykłe podróże Stanisława Twardo w świetle niepublikowanych wspomnień - Olkuśnik, Marek (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The article is devoted to Stanisław Twardo: a member of the Polish independence movement before 1918 and the outstanding governmental activist between 1918 and 1939. In those years Twardo was the founder of modern, professional Polish administration and the governor of the Warsaw province (1927–1934). After World War II, during the Stalinian period, he was a political prisoner. Twardo left the extremely interesting, unpublished memoirs. Currently they are kept in the National Library in Warsaw. The important part of Twardo’s memoirs talks about travels and tourist trips that the author undertook in his entire life. This article characterizes the journeys from the époque before World War I. In the first place are the youthful trips in which Twardo took part with his school friends. Young boys hiked as the pedestrians through the Polish territories that were under the Russian annexation at that time. The pupils admired wild nature and visited historical monuments. As a student Twardo travelled to the southern Ukraina and The Crimean Peninsula. He participated in the canoeing trip on the Dnepr river – close to its famous waterfalls. At the time of a few-month stay in Paris the author visited all the historical and cultural places of the French capital. The homecoming to Warsaw let him for visiting historical German cities and a boat-voyage on the Rhine river. The most interesting part of the memoirs connected with the tourist customs is the account of two Alpine trips that Twardo made in 1911 and 1913. They both were rough, demanding treks. In the case of Polish society such way of travelling was extremely rare at that time. Each of those trips was ended by the visits to famous cities in the northern Italy. The characteristic features of Twardo’s journeys were: extraordinary good preparation, sophisticated choice of destinations, ability to bear difficult conditions, the reduced costs and skills for saving the money. In my opinion the tourist activities of Stanisław Twardo symbolize the attempts of different circles of the Warsaw middle class to manifest their own social position and ambitions. His travels confirm the theory of British sociologist John Urry (The Tourist Gaze) who claims that travels and tourism are important factors which shape social structure and determine the place of different groups in a society.